Description of Hemoglobin Levels for Pregnant Women Workers of The Djarum Cigarette Factory at The Mejobo Kudus Health Center - Budi Santosa; Hasna Widad Salsabila; Andri Sukeksi (Universitas Muhammadiyah Semarang, 2023)
During pregnancy a woman is very susceptible to disorders of low levels of hemoglobin in the blood. Low hemoglobin values are associated with clinical problems such as anemia. Anemia can be more severe due to several factors, such as trimester of pregnancy, type of work, education, infectious diseases and so on. Most of the pregnant women in the Kudus Regency are pregnant women who work in cigarette factories. Pregnant women who work in cigarette factories will have an impact on their pregnancy, based on the theory that tobacco as a raw material for cigarettes contains addictive substances that are harmful to health. The purpose of this study was to find out the description of hemoglobin in pregnant women working in the Djarum cigarette factory at the Mejobo Kudus Health Center. This type of research is descriptive. The research was carried out in May 2022 and the examination was carried out at the Mejobo Health Center. Sampling with purposive sampling technique as many as 25 respondents. Analysis and data processing using tables. The results obtained from 25 respondents mostly had an average hemoglobin level of 12.3 g/dl, where the majority of respondents had normal hemoglobin of 88%. The majority of respondents do not experience anemia, this can occur because when working pregnant women use complete APD, from head coverings, masks, and aprons to protect themselves.